EFEKTIVITAS MODEL LEARNING START WITH A QUESTION (LSQ) TERHADAP HASIL BELAJAR PPKN PADA SISWA KELAS IVA SD INPRES TETEBATU KABUPATEN GOWA - Nadhifah, Yahyun; Rismawati; aba, Akbar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Question (LSQ) model on the learning outcomes of Civics Education (PPKn) among fourth-grade students at SD Inpres Tetebatu, Gowa Regency. The study employed a quantitative approach with a quasi-experimental design using a nonequivalent control group design. The sample consisted of class IVA as the experimental group and class IVB as the control group, with a total of 65 students. Data were collected through learning outcome tests and observation sheets, and analyzed using descriptive and inferential statistics, including tests of normality, homogeneity, and an independent sample t-test. The results showed that the LSQ model was effective in improving students’ learning outcomes. The average score of the experimental group increased from 61 to 82, with learning mastery improving from 45% to 100%. In contrast, the control group showed a smaller increase, from 53 to 61, with mastery improving from 28% to 38%. The hypothesis testing indicated that t-count (3.521) > t-table (1.998) with a significance value of 0.001 < 0.05, meaning that H₁ was accepted. In addition, the observation results showed that the implementation of the learning process reached 86% (high category). Thus, the Learning Start With a Question (LSQ) model is effective in improving the learning outcomes of Civics Education (PPKn) among fourth-grade students at SD Inpres Tetebatu, Gowa Regency.